The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1080/10872981.2023.2175620
|View full text |Cite
|
Sign up to set email alerts
|

Novel COVID-19 vaccine hesitancy and acceptance, and associated factors, amongst medical students: a scoping review

Abstract: Medical students are likely to be exposed to COVID‐19 patients so achieving high vaccination coverage rates for this group of healthcare workers is important, as is their potential as vaccination role models. The aim of this scoping review was to evaluate the current literature to determine the rates of COVID-19 vaccine hesitancy and acceptance, and associated factors, amongst medical students. Systematic searches of the Medline Ovid, Embase, PubMed, and Education Resources Information Centre (ERIC) online dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…Among these articles, a prevailing theme emerged regarding the dynamics of vaccine acceptance versus hesitancy. A notable majority, comprising 51 articles, indicated that the willingness to receive vaccination outweighed hesitancy [5,6]. The vaccine hesitancy appeared to be more pronounced during the initial stages of the pandemic when COVID-19 was still considered novel.…”
Section: Resultsmentioning
confidence: 99%
“…Among these articles, a prevailing theme emerged regarding the dynamics of vaccine acceptance versus hesitancy. A notable majority, comprising 51 articles, indicated that the willingness to receive vaccination outweighed hesitancy [5,6]. The vaccine hesitancy appeared to be more pronounced during the initial stages of the pandemic when COVID-19 was still considered novel.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, COVID-19 vaccination did not appear to have a significant effect on HA levels. Given the impact of vaccination on the immune response and the development of novel vaccine technologies, it is necessary to further evaluate their potential role in HA production and other important physiological processes (Pandher and Bilszta, 2023).…”
Section: Discussionmentioning
confidence: 99%